The Effect of Growth Strategies on Degree of Internationalization: A Study on Turkish Exporters - SANCAK, FATİH MEHMET and TANYERİ, Mustafa (International Journal of Contemporary Economics and Administrative Sciences, 2021)
The phenomenon of globalization, which has become widespread since the last quarter of the last century, is one of the most important elements that come to the forefront in the development and becoming hegemonic of neoliberal ideology. In this article the relationship of firm characteristics and the degree of internalization has been examined and the mediating effect of international growth strategies of the top 1000 exporting Turkish companies has been analysed. It has been detected that international growth strategies have a mediating effect between firm characteristics and the degree of internalization. Another contribution of the study is the result that R&D has a positive effect on the International growth strategies and degree of internalization. This research will also be a guide for developing firms in Turkey for selecting the right international growth strategies and form their firm characteristics in order to be successful during their globalization process.